Three Decades (1992-2021) Of Green Consumer Behaviour: A Bibliometric Analysis Its Publication, Year And Percentage (Journal of Pharmaceutical Negative Results, 2023)
Since consumers are focusing more on environmental sustainability, researchers are also becoming interested in studying the behaviour of such consumers. This study carried out a bibliometric analysis of green product and the purchase behavior of consumers starting from 1992 to 2021. The Scopus database was searched to find the most cited papers, prolific authors, countries, and institutions related to green product purchase behaviour. The purpose of this study is to provide a bibliometric analysis of green product related literature. The study utilized the Boolean search technique to retrieve the publications from 1992 to 2021 related to perception, awareness, attitude, and purchase intention of consumers towards green products. Number of 764 research paper studies were extracted to give instructive and delegate points of view of the information. The outcomes of the bibliometric analysis shown that most publications on green branding were published in 2018. The most recognised study is titled ‘Pro-environmental products: marketing influence on consumer buying decision.’ Chung-Shing Chan of The Chinese University of Hong Kong is recognised the most popular writer on green branding. Journal of Cleaner Production and Sustainability have published the most literature on green products. Moreover, this study provides information on significant journals, authors, institutions, and countries on the topic of environmental sustainability and green research. Further, this study documented that developing countries dominated the publication of research on green products. In terms of higher education institutions, Malaysia and China took the lead in publishing of green product related research.